Knowledge And Self Efficiency Of Nurses Regarding Early Initiation Of Cardiopulmonary Resuscitation In Selected Hospital In Alqundah Region (The Review of Diabetic Studies, 2024)
This study aimed to study the nurses knowledge and self-efficacy about the cardiopulmonary resuscitation at Al-Qunfudhah region, KSA. Knowledge is defined as the understanding, skill development, Apprehension, expertise enhancement, proficiency and realization regarding the Scenario, construct, event, or any other situation.Objective: This research aimed to assess the relationship between nurses’ knowledge and self-efficacy regarding the early initiation of CPR and automated defibrillation of cardiac arrest patients. Methods: The study measured the nurse’s knowledge regarding cardiopulmonary resuscitation, the adopted scale is consisting of 20 items with four-point response option with 5 subscales. Descriptive statistics and Pearson correlation used for data analysis.Results: Overall, the study sample showed very low knowledge regarding early initiation of CPR, compared to very high incorrect answer. Moreover, the participant respond (0.0%) for high score of knowledge. Conclusion: It is important for the nurses to be at a high level of skill and knowledge in this field. Because increasing levels of knowledge of nursing staff will support their own effectiveness.